Chemical compositions and biological activities of essential oils of Beilschmiedia glabra - Wan Salleh, Wan Mohd. Nuzul Hakimi (Natural Product Incorporation, 2015)
This study was designed to examine the chemical compositions of essential oils from Beilschmiedia glabra and their antioxidant, antimicrobial, antityrosinase, acetylcholinesterase and anti-inflammatory activities. In total, 47 components were identified in the essential oils, which made up 86.8% and 89.7% of the leaf and bark oils, respectively. The leaf oil is composed mainly of β-eudesmol (15.4%), β-selinene (12.2%), caryophyllene oxide (8.1%) and γ-gurjunene (5.2%), while the bark oil contains high percentages of β-eudesmol (19.3%), β-selinene (16.9%), δ-cadinene (15.8%), germacrene D (9.8%) and β-caryophyllene (5.5%). Antioxidant activity showed that the leaf oil has the highest phenolic content at 233.4 mg GA/g, while the bark oil showed potent activity in the β- carotene/linoleic acid bleaching assay. However, both oils showed weak activity in the DPPH and ABTS assays. For antimicrobial activity, the leaf and bark oils displayed strong activity against Candida glabrata and Saccharomyces cerevisiae with MIC values of 31.3 and 62.5 μg/mL, respectively. Percentage inhibitions against tyrosinase (leaf 73.7%; bark 76.0%) and acetylcholinesterase (leaf 48.1%; bark 45.2%) were tested at a concentration of 1 mg/mL, while anti-inflammatory activity (leaf 59.7%; bark 48.9%) was evaluated at a concentration of 100 μM. Evaluation of these assays indicated moderate levels of activity.